2022
DOI: 10.1007/s11136-022-03215-x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis assessed with a new screening tool and oral health-related quality of life: cross-sectional findings among general-population adults

Abstract: Introduction Periodontitis, as a chronic, multifactorial inflammatory disease, has complex relationships with other diseases and ultimately with well-being. The aim of this cross-sectional study was to investigate the association between self-report periodontitis, as measured with the recently developed and validated modified Periodontal Screening Score (mPESS), and oral health-related quality of life (OHRQol) in a large population-based sample derived from the French NutriNet-Santé e-cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 77 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…These findings were different from those of the literature, as our study included patients with circulatory system diseases who were under periodic control. Another aspect that may have been responsible for the differences between the results is the various methods used to classify periodontal diseases observed in other studies 6,14,16,20,21 .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…These findings were different from those of the literature, as our study included patients with circulatory system diseases who were under periodic control. Another aspect that may have been responsible for the differences between the results is the various methods used to classify periodontal diseases observed in other studies 6,14,16,20,21 .…”
Section: Discussionmentioning
confidence: 92%
“…Our findings showed that older adults had lower values for the domains "Physical functioning" and "Role-physical" in the SF-36 questionnaire. Other studies have shown that age can be a factor that influences quality of life, as well as chronic systemic diseases 4,6,21 . Considering individuals with different degrees of severity of periodontal disease, we observed differences in the "Pain" domain (SF-36), with patients with gingivitis/periodontal health having the worst results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The OHIP was validated in different target populations, e.g., in prosthodontic patients [ 10 , 13 , 14 ], malocclusion patients [ 8 ], patients with removable dentures [ 11 ], edentulous subjects [ 12 ], among the elderly [ 9 ]. In the literature, special attention is paid to the measurement of OHRQoL in patients with periodontal disease and to the application of the OHIP inventory for this purpose [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%